TRUMPOLOGI “MAGA” DALAM TINJAUAN TEORI KOMUNIKASI IDENTITAS DAN KOMUNIKASI POPULIS - Didin Sabarudin (KOMUNIKA BANGSA, 2026)
The United States has undergone drastic changes since Donald Trump took office. The changes brought about by the Make America Great Again! (MAGA) discourse have shaped personal and communal identities, connecting with many nations around the world, creating the hyper-individualism of Trumpology. Trump is a brand, a strategy, entertainment, a spectacle, and politics. Trump is the instrumentalizer of everything around him and the absolute ruler who aims to make the United States a world leader by managing the country and the world like a corporation, which will undoubtedly expand Trump's political and economic interests. Like other ideologies, Trumpology requires hegemony, with Trump's admirers as the brand and the leader as public visibility. As a media spectacle, Trump has two dimensions. On the one hand, Trump understands how to present himself as a scandalous spectacle to attract media attention. On the other hand, the media also needs Trump's figure to present a spectacle that attracts a large audience. Controversy and symbiosis are the two poles of the Trump spectacle dialectic that drives profitability. By creating news in the media, the media creates Trump. This fact provides a realistic picture of capitalism, by definition Trump is a capital accumulation machine that operates on and off with the economy as its input and output. However, populist communication does not imply a general obligation to lie whenever the truth is advantageous, which serves to stimulate agonism, articulate popular identities, and keep the public mobilized. This paper uses critical discourse analysis to uncover the relationship between the Make America Great Again! discourse and Trumpology.